Resources
Testimonials
Plans
Sign in
Sign up
Resources
Testimonials
Plans
AI tutor
Welcome to Bytelearn!
Let’s check out your problem:
Define limit of a function. If
x
2
+
y
2
+
3
x
y
=
7
x^{2}+y^{2}+3xy=7
x
2
+
y
2
+
3
x
y
=
7
, then find
(
d
y
)
/
(
d
x
)
(dy)/(dx)
(
d
y
)
/
(
d
x
)
If
y
=
cos
x
y=\cos x
y
=
cos
x
, then S.T.
y
1
2
+
y
2
=
1
y_{1}^{2}+y^{2}=1
y
1
2
+
y
2
=
1
View step-by-step help
Home
Math Problems
Calculus
Find derivatives of logarithmic functions
Full solution
Q.
Define limit of a function. If
x
2
+
y
2
+
3
x
y
=
7
x^{2}+y^{2}+3xy=7
x
2
+
y
2
+
3
x
y
=
7
, then find
(
d
y
)
/
(
d
x
)
(dy)/(dx)
(
d
y
)
/
(
d
x
)
If
y
=
cos
x
y=\cos x
y
=
cos
x
, then S.T.
y
1
2
+
y
2
=
1
y_{1}^{2}+y^{2}=1
y
1
2
+
y
2
=
1
Identify Equation:
Identify the first equation to differentiate implicitly with respect to
x
x
x
.
Differentiate Implicitly:
Differentiate both sides of
x
2
+
y
2
+
3
x
y
=
7
x^2 + y^2 + 3xy = 7
x
2
+
y
2
+
3
x
y
=
7
with respect to
x
x
x
.
d
d
x
(
x
2
)
+
d
d
x
(
y
2
)
+
d
d
x
(
3
x
y
)
=
d
d
x
(
7
)
\frac{d}{dx}(x^2) + \frac{d}{dx}(y^2) + \frac{d}{dx}(3xy) = \frac{d}{dx}(7)
d
x
d
(
x
2
)
+
d
x
d
(
y
2
)
+
d
x
d
(
3
x
y
)
=
d
x
d
(
7
)
2
x
+
2
y
d
y
d
x
+
3
(
y
+
x
d
y
d
x
)
=
0
2x + 2y\frac{dy}{dx} + 3(y + x\frac{dy}{dx}) = 0
2
x
+
2
y
d
x
d
y
+
3
(
y
+
x
d
x
d
y
)
=
0
Solve for
d
y
d
x
\frac{dy}{dx}
d
x
d
y
:
Solve for
d
y
d
x
\frac{dy}{dx}
d
x
d
y
.
2
y
d
y
d
x
+
3
x
d
y
d
x
=
−
2
x
−
3
y
2y\frac{dy}{dx} + 3x\frac{dy}{dx} = -2x - 3y
2
y
d
x
d
y
+
3
x
d
x
d
y
=
−
2
x
−
3
y
d
y
d
x
(
2
y
+
3
x
)
=
−
2
x
−
3
y
\frac{dy}{dx}(2y + 3x) = -2x - 3y
d
x
d
y
(
2
y
+
3
x
)
=
−
2
x
−
3
y
d
y
d
x
=
−
2
x
−
3
y
2
y
+
3
x
\frac{dy}{dx} = \frac{-2x - 3y}{2y + 3x}
d
x
d
y
=
2
y
+
3
x
−
2
x
−
3
y
Identify Second Equation:
Identify the second equation
y
=
cos
x
y = \cos x
y
=
cos
x
to differentiate directly.
Differentiate Directly:
Differentiate both sides of
y
=
cos
x
y = \cos x
y
=
cos
x
with respect to
x
x
x
.
d
y
d
x
=
−
sin
x
\frac{dy}{dx} = -\sin x
d
x
d
y
=
−
sin
x
Evaluate at
x
=
1
x=1
x
=
1
:
Evaluate
d
y
d
x
\frac{dy}{dx}
d
x
d
y
at
x
=
1
x = 1
x
=
1
for
y
=
cos
x
y = \cos x
y
=
cos
x
.
d
y
d
x
∣
(
x
=
1
)
=
−
sin
(
1
)
\frac{dy}{dx}\bigg|_{(x=1)} = -\sin(1)
d
x
d
y
∣
∣
(
x
=
1
)
=
−
sin
(
1
)
Find
y
(
1
)
y(1)
y
(
1
)
:
Use the given
y
(
1
)
2
+
y
2
=
1
y(1)^2 + y^2 = 1
y
(
1
)
2
+
y
2
=
1
to find
y
(
1
)
y(1)
y
(
1
)
.
cos
(
1
)
2
+
y
2
=
1
\cos(1)^2 + y^2 = 1
cos
(
1
)
2
+
y
2
=
1
y
2
=
1
−
cos
(
1
)
2
y^2 = 1 - \cos(1)^2
y
2
=
1
−
cos
(
1
)
2
y
(
1
)
=
1
−
cos
(
1
)
2
y(1) = \sqrt{1 - \cos(1)^2}
y
(
1
)
=
1
−
cos
(
1
)
2
More problems from Find derivatives of logarithmic functions
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
cos
(
x
)
f(x) = \cos(x)
f
(
x
)
=
cos
(
x
)
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 10 months ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
tan
(
x
)
f(x) = \tan(x)
f
(
x
)
=
tan
(
x
)
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
e
x
f(x) = e^x
f
(
x
)
=
e
x
\newline
f
′
(
x
)
=
f'\left(x\right) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
ln
(
x
)
f(x) = \ln(x)
f
(
x
)
=
ln
(
x
)
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
tan
−
1
x
f(x) = \tan^{-1}{x}
f
(
x
)
=
tan
−
1
x
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
x
e
x
f(x) = x e^x
f
(
x
)
=
x
e
x
\newline
f
′
(
x
)
=
f'\left(x\right) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
e
x
x
f(x) = \frac{e^x}{x}
f
(
x
)
=
x
e
x
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
e
(
x
+
1
)
f(x) = e^{(x + 1)}
f
(
x
)
=
e
(
x
+
1
)
\newline
f
′
(
x
)
=
f'\left(x\right) =
f
′
(
x
)
=
______
Get tutor help
Posted 10 months ago
Question
Find the derivative of
f
(
x
)
f(x)
f
(
x
)
.
\newline
f
(
x
)
=
x
+
3
f(x) = \sqrt{x+3}
f
(
x
)
=
x
+
3
\newline
f
′
(
x
)
=
f'(x) =
f
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Question
Find the derivative of
g
(
x
)
g(x)
g
(
x
)
.
\newline
g
(
x
)
=
ln
(
2
x
)
g(x) = \ln(2x)
g
(
x
)
=
ln
(
2
x
)
\newline
g
′
(
x
)
=
g^{\prime}(x) =
g
′
(
x
)
=
______
Get tutor help
Posted 1 year ago
Related topics
Algebra - Order of Operations
Algebra - Distributive Property
`X` and `Y` Axes
Geometry - Scalene Triangle
Common Multiple
Geometry - Quadrant